ASSESSMENT OF ELDERLY BLOOD PRESSURE WITH BACKWARD TANDEM WALK INTERVENTION - Sarah, Maita (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
Blood pressure is the impulse generated by the walls of the arteries, which are then pumped from the heart throughout the body. In maintaining balance in the elderly, physical exercise is needed to prevent the risk of falling. One of the exercises that can be done is a balance exercise by using a backward tandem walk. This exercise is intended to improve the lateral part of the postural balance, train the attitude or position of the body, control balance, muscle coordination and body movements of the elderly. This study aimed to analyze the effect of assessing blood pressure in the elderly after and before the backward tandem walk intervention. The design used was the Pre-Experimental with the Pre-Post design approach with a sample of 60 elderly respondents who were taken using a non-probability sampling technique and also a consecutive sampling technique. The independent variable is the backward tandem walk exercise while the dependent variable is blood pressure. Blood pressure measurement using observation sheet pre and post-backwards tandem walk exercise. The data were analyzed and then obtained a p-value of 0.000 (<0.005) meaning that there was a difference in blood pressure before and after treatment. From the mean results, it is known that there is an effect of blood pressure on the elderly. The results of the study imply that the backward tandem walk exercise for the elderly is carried out routinely, especially for the elderly with hypertension.